G/M/N Queuing Model-Based Research on the Parking Spaces for Primary and Secondary School - Yi Zhao; Zhen Zhou; Qilong Pan; Tianhua Zhou (Discrete Dynamics in Nature and Society)
In order to ease the traffic congestion near primary and secondary schools during the drop-off and pick-up, traffic behavior was analyzed, and a quantitative allocation method for parking spaces was proposed. The proposed method includes three steps. Firstly, a vehicle queuing model based on G/M/N queue theory was built, and MATLAB was employed to simulate the queuing model to obtain a reasonable parking space for drop-off. Secondly, the reasonable parking space for pick-up is determined based on the cumulative number of vehicles. Finally, an optimization model for the scale of total parking spaces and the short-term parking spaces was proposed to achieve maximum utilization of parking spaces. An empirical analysis and verification were conducted based on actual traffic data of schools. The results show that the proposed model can analyze the overall scale of the parking space for primary and secondary school, as well as the scale of the short-term parking spaces. And the proposed scale of the parking space can well meet the actual parking demand.